MENINGKATKAN HASIL BELAJAR DENGAN METODE CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PENDIDIKAN KEWARGANEGARAAN SDN 16 MUNDUN PEJUGAN - Adam, Fransisco; Sukristin, Sukristin; Pika, Katarina (JURNAL PENDIDIKAN DASAR, 2024)
Abstract: This research is a Classroom Action Research (PTK) with the research objective to improve student learning outcomes on the material of the relationship between images on the state symbol and the Pancasila precepts with the CTL learning approach. The method of Classroom Action Research (PTK) with research subjects of class III students totalling 10 people consisting of 5 boys and 5 girls. Data collection techniques and instruments are test techniques carried out at the end of each cycle. Data collection instruments in the form of essay questions as many as 5 items. Data analysis techniques using descriptive statistical analysis. The results of the study in cycle I the average value of 10 students was 57.7 cycle II student learning outcomes increased by 14.5 from cycle I to 72.5. thus the use of the Contextual Teaching and Learning (CTL) method in Civics Education lessons is effective in improving the learning outcomes of third grade students of SDN 16 Mundun Pejugan. The conclusion that the Contextual Teaching and Learning (CTL) method can significantly improve student learning outcomes in civic education lessons. Suggestions for teachers and schools can continuously innovate in creating innovative learning so that students can develop their abilities optimally.Keywords: Civics Learning Outcomes, Contextual Teaching and Learning Method